KARAKTERISTIK INDEKS MASSA TUBUH DAN JENIS KELAMIN PASIEN HIPERTENSI DI RS IBNU SINA MAKASSAR NOVEMBER 2018 - rachmat faisal syamsu; siska nuryanti; muhammad yastrib semme (J-KESMAS: Jurnal Kesehatan Masyarakat, 2021)
Hypertension, commonly referred to as high blood pressure, is a global health problem in Indonesia because of its high prevalence, although it varies in different countries. In Indonesia, hypertension is found in 83 per 1000 household members. The majority of high blood pressure increases with the presence of risk factors such as; Age, lack of exercise / physical activity, genetic factors and family history, body weight/obesity, sodium intake, alcohol consumption, smoking, stress. This study is a descriptive design using an observational approach to describe the characteristics of the risk factors for the Body Mass Index (BMI) and the gender of hypertension patients at Ibnu Sina Hospital for November 2018. The sampling technique used the total sampling technique with a complete sample size of 26 people. The results showed that the gender characteristics of hypertension sufferers showed that the number of female patients (16 people) was more than that of male patients (10 people). And the attributes of BMI in patients with hypertension found that the number of patients with normal nutritional status (13 people) was the most compared to another nutritional status.